2015
DOI: 10.1097/md.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

The Transforming Growth Factor-β1 (TGF-β1) Gene Polymorphisms (TGF-β1 T869C and TGF-β1 T29C) and Susceptibility to Postmenopausal Osteoporosis

Abstract: The aim of the present study was to integrate all the eligible studies and investigate whether the transforming growth factor-β1 (TGF-β1) gene polymorphisms (TGF-β1 T869C and TGF-β1 T29C) are correlated with postmenopausal osteoporosis (PMOP) risk.PMOP is a common skeletal disease and several genetic factors play an important role in the development and progression of PMOP. Significant associations between TGF-β1 gene polymorphisms (TGF-β1 T869C and TGF-β1 T29C) and PMOP risk have been reported; however, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
11

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 25 publications
0
16
0
11
Order By: Relevance
“…Although evidence of the involvement of these genes in the pathobiology of RCT was already reported, this is the first study to show that SNPs of these genes may modulate the risk of this injury. Both variants were previously reported as a risk factor for several inflammatory and aging‐related diseases, including common musculoskeletal diseases (for rs17576: lumbar disc degeneration; for rs1800470: osteoporosis), diabetes, and dyslipidemia . The association of the studied variants with diabetes and dyslipidemia again reinforces the necessity to add these co‐morbidities as covariables in RCT risk models to identify the SNPs that are independent risk factors.…”
Section: Discussionmentioning
confidence: 55%
“…Although evidence of the involvement of these genes in the pathobiology of RCT was already reported, this is the first study to show that SNPs of these genes may modulate the risk of this injury. Both variants were previously reported as a risk factor for several inflammatory and aging‐related diseases, including common musculoskeletal diseases (for rs17576: lumbar disc degeneration; for rs1800470: osteoporosis), diabetes, and dyslipidemia . The association of the studied variants with diabetes and dyslipidemia again reinforces the necessity to add these co‐morbidities as covariables in RCT risk models to identify the SNPs that are independent risk factors.…”
Section: Discussionmentioning
confidence: 55%
“…These studies strongly suggested that TGF-β1 was protective against COPD development. The TGF-β1 polymorphism rs1982073 is a C→T substitution, resulting in a proline to leucine substitution at codon 10 [ 33 ]. It was reported that the C allele of rs1982073 was associated with higher TGF-β1 mRNA and protein levels [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…26 TGF-b1 T869C/T29C polymorphisms were markedly associated with postmenopausal osteoporosis risk in Asians, not in Caucasians. 27 CC genotype and T allele of TGF-b1 T869C polymorphism were distinctly associated with diabetic nephropathy risk in the Asian population. 28 Furthermore, larger number of studies should be performed to compare the differences between Asians and Caucasians.…”
Section: Discussionmentioning
confidence: 99%